PREVALANCE OF CANDIDIASIS IN CHILDREN IN MUMBAI - Wandre, Shrutika; Sanap, Swati; Mukadam, Tehmeena; Vaidya, Shashikant; Chowdhary, Abhay (LIFE: International Journal of Health and Life-Sciences, 2015)
This study aims to determine the prevalence of infection of Candida species and its resistance to anti-fungal agents amongst children in Mumbai. Total 169 clinical isolates of Candida species from various clinical specimens namely blood, urine, stool; Cerebral spinal fluid, liver abscess,Endotracheal secretion and ventric tip were included in the study. They were screened and identified by staining, culture and microscopy, followed by isolation on specialized chromogenic agar. Antifungal susceptibility tests of these isolates were carried out against Amphotericin B (50mcg), Itraconazole (10mcg), Clotrimazole (10mcg), Ketoconazole (30mcg), Miconazole (30mcg), and Fluconazole (10mcg) and were reported based on CLSI guidelines (2008).The prevalence of Candida infections was found to be greater in males (69%) as compared to female (31%) children. In the age group of 0-5 years, the occurrence of Candida infection was substantially higher as compared to the others age group. Candida albicans was found to be the major causative agent of fungal infections. The susceptibility of isolates to antifungal agents was found to differ in male and female patients. Overall, highest resistance was observed to Fluconazole (27.1%) while, lowest resistance to Amphotericin B (28.7%). Males exhibited highest resistance to Fluconazole (27.1%) while, females showed highest resistance to Amphotericin B (28.7%). Higher resistance was found to the azole group of antifungal agents. Hence, Amphotericin B can be the choice of treatment of Candida infection in children followed by Miconazole.